The putative amino acid ABC transporter substrate-binding protein AapJ2 is necessary for Brucella virulence at the early stage of infection in a mouse model - Tian, Mingxing (Vet Res, 2018)
Brucellosis is a zoonotic bacterial disease caused by Brucella spp. The virulence of these bacteria is dependent on their ability to invade and replicate within host cells. In a previous study, a putative gene bab_RS27735 encoding an amino acid ABC transporter substrate-binding protein homologous to AapJ protein was found to be involved in Brucella abortus virulence. In this study, we successfully constructed a bab_RS27735 deletion mutant, Δ27735. Compared with the wild-type strain, the lipopolysaccharide pattern of the mutant was not changed, but the growth ability was slightly defected in the exponential phase. In tolerance tests, sensitivity of the Δ27735 mutant to oxidative stress, bactericidal peptides or low pH was not different from that of the wild-type strain. Cell infection assay showed that the mutant was reduced survival within macrophages but could efficiently escape lysosome degradation. The results of a virulence test showed that the Δ27735 mutant was attenuated in a mouse model at the early stage of infection but recovered its virulence at the late stage of infection. Meanwhile, the development of splenomegaly and histopathological lesions was observed in mice infected with either the wild-type strain or the mutant. These results are in line with the release of IL-12p40 and TNF-α into the peripheral blood of infected mice. Besides, expression of diverse genes was up-regulated in the Δ27735 mutant, which may contribute to the reduced virulence of the mutant. These data elucidated that the bab_RS27735 gene is necessary for B. abortus virulence at the early stage of infection in a mouse model.